2013
DOI: 10.1002/humu.22331
|View full text |Cite
|
Sign up to set email alerts
|

Relevance of Different Cellular Models in Determining the Effects of Mutations on SLC16A2/MCT8 Thyroid Hormone Transporter Function and Genotype-Phenotype Correlation

Abstract: SLC 16A2, the gene for the second member of the solute carrier family 16 (monocarboxylic acid transporter), located on chromosome Xq13.2, encodes a very efficient thyroid hormone transporter: monocarboxylate transporter 8, MCT8. Its loss of function is responsible in males for a continuum of psychomotor retardation ranging from severe (no motor acquisition, no speech) to mild (ability to walk with help and a few words of speech). Triiodothyronine uptake measurement in transfected cells and, more recently, pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
24
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 18 publications
3
24
0
Order By: Relevance
“…This therefore plays a decisive role in why a precise established relationship does not exist between the genotype, molecular characteristics of MCT8 variants (localization, transport routes), and the severity of patient phenotypes (Visser et al 2011) (summarized in Supplementary Table 1). The functional characteristics of the MCT8 mutants investigated in this current study were previously explored by in vitro analyses using JEG, MDCK, or COS cells (Schwartz et al 2005, Kinne et al 2009, 2010, Capri et al 2013, Groeneweg et al 2014. The cellular localization of MCT8 mutants and the rates of thyroid hormone uptake for all of these mutants finally revealed a diminished rate of T3 uptake.…”
Section: Substrate Uptake Of Wt and Mutant Variants Of Mct8 In Cos-7 mentioning
confidence: 92%
See 2 more Smart Citations
“…This therefore plays a decisive role in why a precise established relationship does not exist between the genotype, molecular characteristics of MCT8 variants (localization, transport routes), and the severity of patient phenotypes (Visser et al 2011) (summarized in Supplementary Table 1). The functional characteristics of the MCT8 mutants investigated in this current study were previously explored by in vitro analyses using JEG, MDCK, or COS cells (Schwartz et al 2005, Kinne et al 2009, 2010, Capri et al 2013, Groeneweg et al 2014. The cellular localization of MCT8 mutants and the rates of thyroid hormone uptake for all of these mutants finally revealed a diminished rate of T3 uptake.…”
Section: Substrate Uptake Of Wt and Mutant Variants Of Mct8 In Cos-7 mentioning
confidence: 92%
“…Extensive functional in vitro characterization of MCT8 mutants revealed that the results obtained might vary depending on the cellular system used (Jansen et al 2005, Kinne et al 2009, Capri et al 2013. This therefore plays a decisive role in why a precise established relationship does not exist between the genotype, molecular characteristics of MCT8 variants (localization, transport routes), and the severity of patient phenotypes (Visser et al 2011) (summarized in Supplementary Table 1).…”
Section: Substrate Uptake Of Wt and Mutant Variants Of Mct8 In Cos-7 mentioning
confidence: 99%
See 1 more Smart Citation
“…SIFT software predicted that SLC16A2 c.671C>T (p.A224V) and c.661G>A (p.G221R) would be tolerated. However, these variants were predicted to be deleterious by PolyPhen-2 and CADD score and proven to be pathogenic by in vitro functional analysis [19,20]. The p.W398R mutation has not been reported previously, and it is not present in the gnomAD browser; Polyphen-2, SIFT, and CADD score classified this variant as pathogenic.…”
Section: Molecular Analysis Of the Thrb And Slc16a2 Genesmentioning
confidence: 98%
“…1b). Among them, the p.I188N, p.G221R, p.A224V, p.G276R, and p.G401R mutations have previously been reported to be pathogenic [15,[19][20][21][22]. Four patients inherited their mutations from their mothers.…”
Section: Molecular Analysis Of the Thrb And Slc16a2 Genesmentioning
confidence: 99%